Optimization of The Addition Of Polivinil Alcohol (PVA) as A Plasticizer In Biofilm with Tapioca-Chitosan Flour Material - Tri Aminingsih; Leny Heliawati; Muhammad Fathurrahman (Helium: Journal of Science and Applied Chemistry, 2021)
The addition of a plasticizer, namely polyvinyl alcohol (PVA) as a plasticizer, will increase flexibility and prevent the polymer from cracking. The purpose of this study was to compare the mechanical properties of biofilms from tapioca-chitosan flour with or without the addition of polyvinyl alcohol (PVA) and determine the mass of polyvinyl alcohol (PVA) which can provide optimum mechanical properties of biofilms, test the biodegradability of biofilms and polypropylene plastics and to analyze biofilms using FT-IR. The making of biofilm from 4% tapioca flour and 2% chitosan was carried out by adding variations of polyvinyl alcohol as much as 0, 1, 2, 3, 4 and 5 grams to each tapioca-chitosan flour solution. The effect of adding polyvinyl alcohol (PVA) can be seen from the results of the tensile strength test, the breaking length test, the water resistance test and the biodegradability test. The resulting biofilm functional group analysis was performed by FT-IR. The results showed that the addition of PVA could increase the tensile strength and breaking length, but decreased the water resistance of the biofilm. The optimum mechanical properties of tapioca-chitosan flour biofilm resulted from the addition of 3 grams of PVA with a tensile strength of 2.163 kgf / cm2, the breaking length of 13.64% and 12.46% of absorbed water. Biofilms can be degraded by the fungus Aspergilus niger. The results of biofilm analysis using FTIR indicate the presence of functional groups (CH, NH2, NH, OH, CO and CN) which are the functional groups of the biofilm constituent materials. The optimum mechanical properties of tapioca-chitosan flour biofilm resulted from the addition of 3 grams of PVA with a tensile strength of 2.163 kgf / cm2, the breaking length of 13.64% and 12.46% of absorbed water. Biofilms can be degraded by the fungus Aspergilus niger. The results of biofilm analysis using FT-IR indicate the presence of functional groups (CH, NH2, NH, OH, CO and CN) which are the functional groups of the biofilm constituent materials.